Impact of lipopolysaccharides on cultivation and recombinant protein expression in human embryonal kidney (HEK‐293) cells. Issue 11 (25th October 2021) - Faust, Christine; Beil, Christian; Dittrich, Werner; Rao, Ercole; Langer, Thomas
Abstract: The human embryonal kidney 293 cell (HEK‐293) is a widely used expression host for transient gene expression. The genes or plasmids used for the transient transfections are usually propagated and extracted from the gram‐negative bacterium Escherichia coli, the workhorse for molecular biologists. As a gram‐negative bacterium E. coli has an outer membrane (OM) containing lipopolysaccharides (LPS) or endotoxins. LPS are very potent inducers of inflammatory cytokines in the body. In early research phases DNA intended for transient transfections is not routinely checked for LPS‐levels. In this study we addressed the question whether LPS has an impact on the cultivation and production of a recombinant antibody. At high concentrations the presence of LPS has a detrimental impact on cell viability and recombinant protein expression. But low LPS concentrations are tolerated and might even enhance protein expression levels.